REVIEW OF WASTEWATER FROM THE CITY OF OUAGADOUGOU: SELF-PURIFICATION CAPACITY FOR THE PRODUCTION OF BIOGAS/BILAN DES EAUX USEES DE LA VILLE DE OUAGADOUGOU : CAPACITE AUTO-EPURATOIRE EN VUE DE LA PRODUCTION DE BIOGAZ - Zongo, Inoussa; Diallo-Kone, Martine; Palm, Kalifa; Tiemtore, Ablasse; Sanogo, Oumar; Guiguemde, Edouard; Lapicque, Francois; Leclerc, Jean-Pierre (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2012)
The two tests realized in this study show that the anaerobic conditions are better than the aerobic ones in order to treat most of the effluents of Ouagadougou in Burkina Faso. This essay allows 95% reduction of greenhouse gases specifically CO2 by anaerobic way. The survey of effluent gives 14 456 000 m3 yr-1 with 3716 mg O2 L-1 COD and 790 520 m3 yr-1 of industrial wastewater with 2 238 mg O2 L-1. The potential of biogas based on the domestic wastewater is evaluated to 29 434 m3 per day.